Influence of Type I Interferons in Gammaherpesvirus-68 and Its Influence on EAE Enhancement - Márquez, Ana Citlali; Croft, Carys; Shanina, Iryna; Horwitz, Marc Steven (Frontiers in Immunology, 2022)
Epstein-Barr virus (EBV) has been identified as a putative trigger of multiple sclerosis (MS). Previously, we reported that mice latently infected with murine gammaherpesvirus 68 (γHV-68), the murine homolog to EBV, and induced for experimental autoimmune encephalomyelitis (EAE), developed an enhanced disease more reminiscent of MS. These prior results showed that expression of CD40 on CD11b+CD11c+ cells in latently infected mice was required to prime the strong Th1 response driving disease as well as decreasing Treg frequencies in the periphery and CNS. Subsequent work demonstrated that transfer of B cells from latently infected mice was sufficient to enhance disease. Herein, we show that B cells from infected mice do not need type I IFN signaling to drive a strong Th1 response, yet are important in driving infiltration of the CNS by CD8+ T cells. Given the importance of type I IFNs in MS, we used IFNARko mice in order to determine if type I IFN signaling was important in the enhancement of EAE in latently infected mice. We found that while type I IFNs are important for the control of γHV-68 infection and maintenance of latency, they do not have a direct effect in the development of enhanced EAE.